188k views
0 votes
Select the correct answer.

Select the correct answer.-example-1
User Axiixc
by
5.1k points

1 Answer

6 votes

Answer:

B

Explanation:

With limits, the first thing one should always try is direct substitution. Therefore, let's try that.


\lim_(x \to 1) ((x^2+1)/(x+1)+x^2+3) \\= (((1)^2+1)/((1)+1)+(1)^2+3) \\=(2)/(2)+1+3\\ =1+4=5

Therefore:


\lim_(x \to 1) ((x^2+1)/(x+1)+x^2+3) =5

User Dicky Tsang
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.